2010
DOI: 10.1037/a0017387
|View full text |Cite
|
Sign up to set email alerts
|

The face in the crowd effect: Anger superiority when using real faces and multiple identities.

Abstract: The "face in the crowd effect" refers to the finding that threatening or angry faces are detected more efficiently among a crowd of distractor faces than happy or nonthreatening faces. Work establishing this effect has primarily utilized schematic stimuli and efforts to extend the effect to real faces have yielded inconsistent results. The failure to consistently translate the effect from schematic to human faces raises questions about its ecological validity. The present study assessed the face in the crowd e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
184
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(202 citation statements)
references
References 23 publications
(34 reference statements)
12
184
2
1
Order By: Relevance
“…This phenomenon has been dubbed the "anger superiority effect", and it has been proposed as one example of the workings of the dominance-submissiveness system in the visual system (Öhman, 2009). Some controversy has been raised about the reliability of the phenomenon (Becker et al, 2011), but it has been convincingly shown, at least with faces of males (Becker et al, 2007), schematic faces (Öhman, Lundqvist, & Esteves, 2001), and facial expressions of prototypical emotions (Pinkham et al, 2010) as stimuli. already noted that the phenomenon is hard to explain without some kind of implicit preattentive processing of the angry faces.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been dubbed the "anger superiority effect", and it has been proposed as one example of the workings of the dominance-submissiveness system in the visual system (Öhman, 2009). Some controversy has been raised about the reliability of the phenomenon (Becker et al, 2011), but it has been convincingly shown, at least with faces of males (Becker et al, 2007), schematic faces (Öhman, Lundqvist, & Esteves, 2001), and facial expressions of prototypical emotions (Pinkham et al, 2010) as stimuli. already noted that the phenomenon is hard to explain without some kind of implicit preattentive processing of the angry faces.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are rooted in evolutionary arguments, proposing a fitness advantage for processing threatening in comparison to nonthreatening environmental stimuli (Bishop, 2008;Horstmann & Bauland, 2006;Pinkham et al, 2010).…”
Section: The Threat Systemmentioning
confidence: 96%
“…Some studies (e.g., Horstmann & Bauland, 2006;Pinkham, Griffin, Baron, Sasson, Gur, 2010) find that threatening or angry faces are detected more efficiently among a crowd than happy or nonthreatening faces. These findings are rooted in evolutionary arguments, proposing a fitness advantage for processing threatening in comparison to nonthreatening environmental stimuli (Bishop, 2008;Horstmann & Bauland, 2006;Pinkham et al, 2010).…”
Section: The Threat Systemmentioning
confidence: 99%
“…For example, in visual search tasks, pictures of snakes elicited faster response times than pictures of flowers in both humans (Öhman, Flykt, & Esteves, 2001) and macaque monkeys (Shibasaki & Kawai, 2009). In addition, faces with an angry expression are detected faster in a visual search task than happy or neutral faces (e.g., Öhman, Lundqvist, & Esteves, 2001;Pinkham, Griffin, Baron, Sasson & Gur, 2010; for a review, see Frischen, Eastwood & Smilek, 2008; but see Becker, Anderson, Mortensen, Neufeld, & Neel, 2011) and search times for emotional faces are not affected by array size (e.g., Eastwood, Smilek & Merikle, 2001;Fox et al, 2000;Juth, Lundqvist, Karlsson, & Öhman, 2005). The faster detection of emotional faces is probably most influenced by the heightened arousal induced by these faces (Lundqvist, Bruce, & Öhman, 2015).…”
Section: Studies On Attentional Processesmentioning
confidence: 99%